Automotive process audits : preparations and tools - Stamatis, D. H., 1947- (Boca Raton : CRC Press, Taylor & Francis Group, 2021)
"With a detailed discussion on the preparation and tools needed for an automotive process audit, this book addresses the fundamental issues and concerns by focusing on two objectives. Explaining the methods and tools used in the process for the organization, and to provide a reference or manual for dealing with documenting quality issues. This book addresses the fundamental issues and concerns for a successful automotive process audit and details specifically how to prepare for it. It presents a complete assessment of what an organization must do to earn certification in ISO standards, industry standards, and customer specific requirements. It also focuses on the efficiency of resources within an organization so that an audit can be successful and describes the methodologies to optimize the process by knowing what to do, what to say, and how to prove it. A road map is offered for the "Process Audit" and the "Layered Audit" and defines a clear distinction between the preparation details for each. This book is intended for those that conduct audits, those who are interested in auditing, and those who are being audited. It specifically addresses how to prepare for an automotive process audit which includes readers that are involved in quality, manufacturing, operations management, and those that work with suppliers"--
OCLC-licensed vendor bibliographic record.
Keywords: Automobiles -- Design and construction -- Quality control; Manufacturing processes -- Quality control; Automobile industry and trade -- Auditing; TECHNOLOGY / Manufacturing; TECHNOLOGY / Engineering / Automotive; TECHNOLOGY / Engineering / Industrial